Spirituality Leadership in Nahdlatul Ulama and Muhammadiyah: Case Study of Vocational High School in Pekalongan Regency - Basit, Agus Abdul; Khanafi, Imam; Untung, Slamet (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
This study aims to analyze the student’s character, the characteristics of the principal’s spiritual leadership, and the practice of applying the principal’s spiritual values in character education of students at SMK NU and SMK Muhammadiyah Kesesi, Pekalongan Regency. This research is descriptive qualitative research with a case study design that seeks to reveal facts and phenomena in detail and thoroughly. In this study, the researcher is the main data collection instrument. The main objects in this study were the principal and students at SMK NU Kesesi and SMK Muhammadiyah. Techniques to collect data using interviews, direct observation, documentation. The validity of the data is obtained by triangulation, continuous observation and re-checking the existing data. The researcher uses the analytical method developed by Miles and Huberman. The findings in this study are (1) There are differences in the characteristics of the headmaster’s spiritual leadership. The researcher identified several characteristics that emerged, including, Innovative and Religious-Nationalist Discipline for NU Kesesi Vocational School and Professional Discipline and Ambitious Responsibilities for Kesesi Muhammadiyah Vocational School; (2) Implementation of religious activities as a foundation for the spirituality of school residents was originally initiated by each headmasters. Both have strong religious backgrounds and environments. Therefore, it can implement character strengthening, habituation, moral knowing, moral feeling and loving, moral feeling, moral modelling, and repentance.